2021
DOI: 10.2147/ppa.s322745
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Sensitivities of Measures of Adherence to Antihypertensive Drugs Using Korean National Health Insurance Claims Data

Abstract: Purpose Numerous studies have utilized various forms of adherence measures. However, methods for measuring adherence are inconsistent. Moreover, few studies are available that have compared sensitivities of the effects of several criteria on medication adherence. This study aims to compare measures of adherence using varied analytical decisions. Materials and Methods We included three measures for adherence: proportion of days covered with one or more medications (PDC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
0
8
0
1
Order By: Relevance
“…As there were no previous studies comparing these 3 measurements in multidrug antihypertensive therapy, it is difficult to directly compare to previous studies. Our previous study of patients receiving both antihypertensive single and multidrug regimens showed similar trends [ 22 ]. However, a previous study comparing adherence to antidiabetic therapy showed different trends; the median value (IQR) of adherence was 95.9% (IQR, 72.3-100) and 77.5% (IQR, 51.8-96.4) when using PDC with≥1 and DPPR, respectively [ 33 ].…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…As there were no previous studies comparing these 3 measurements in multidrug antihypertensive therapy, it is difficult to directly compare to previous studies. Our previous study of patients receiving both antihypertensive single and multidrug regimens showed similar trends [ 22 ]. However, a previous study comparing adherence to antidiabetic therapy showed different trends; the median value (IQR) of adherence was 95.9% (IQR, 72.3-100) and 77.5% (IQR, 51.8-96.4) when using PDC with≥1 and DPPR, respectively [ 33 ].…”
Section: Discussionmentioning
confidence: 71%
“…To compare the measurements of adherence to multidrug antihypertensive therapy and their clinical consequences, we included PDC with≥1 , PDC wm , and DPPR, which had been analyzed in our previous study [ 17 - 20 , 22 ]. First, PDC with≥1 was calculated as the number of days covered by ≥ 1 prescription during the observation period, divided by the number of days from the first prescription to the end of the observation period [ 17 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations